Key Factors in the Success of an Organization's Information Security Culture (Journal of The Colloquium for Information Systems Security Education, 2013)
This research study reviewed relative literature on information security and information security culture within organizations to determine what factors potentially assist an organization in implementing, integrating, and maintaining a successful organizational information security culture. Based on this review of literature, five factors were determined to potentially contribute to a successful information security culture. A survey instrument was designed to determine if each of the factors had a significant association with a successful organizational information security culture, if the factors had a positive or negative relationship with a successful information security culture, and the strength of the relationship to a successful organizational security culture. The data from 200 useable surveys were analyzed using the Chi Square Test of Independence and Bivariate correlation to determine the relation between each of the factors, the independent variables, and the dependent variable, defined as a successful organizational information security culture. The analysis of this data is presented for both scholarly and practitioner information and use.